Approximate Inertial Manifolds of Strongly Damped Nonlinear Wave Equations (Journal of Partial Differential Equations, 1999)
In this paper we consider a class of strongly damped nonlinear wave equations. By the transformation of unknown functions and decomposition of operators, we construct a family of approximate inertial manifolds, and obtain the estimate of orders of approximation of such manifolds to solution orbits.
Keywords: Approximate inertial manifolds; strong damping; nonlinear wave equation